Cerebral Blood Flow and Amyloid-β Interact to Affect Memory Performance in Cognitively Normal Older Adults - Bangen, Katherine J.; Clark, Alexandra L.; Edmonds, Emily C.; Evangelista, Nicole D.; Werhane, Madeleine L.; Thomas, Kelsey R.; Locano, Lyzette E.; Tran, My; Zlatar, Zvinka Z.; Nation, Daniel A.; Bondi, Mark W.; Delano-Wood, Lisa (Frontiers in Aging Neuroscience, 2017)
Cerebral blood flow (CBF) alterations and amyloid-B (AB) accumulation have been independently linked to cognitive deficits in older adults at risk for dementia. Less is known about how CBF and AB may interact to affect cognition in cognitively normal older adults. Therefore, we examined potential statistical interactions between CBF and AB status in regions typically affected in Alzheimer’s disease (AD) within a sample of older adults from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) study. Sixty-two cognitively normal participants (mean age=72 years) underwent neuroimaging and memory testing. Arterial spin labeling (ASL) magnetic resonance imaging (MRI) was used to quantify CBF and florbetapir PET amyloid imaging was used to measure A deposition. AB status (i.e., positivity versus negativity) was determined based on established cutoffs (Landau et al., 2013). The Rey Auditory Verbal Learning Test (RAVLT) was used to assess memory. Linear regression models adjusted for age, education, and sex, demonstrated significant interactions between CBF and AB status on memory performance. Among AB positive older adults, there were significant negative associations between higher CBF in hippocampus, posterior cingulate, and precuneus and poorer memory performance. In contrast, among AB negative older adults, there were no significant associations between CBF and cognition. Our findings extend previous CBF studies of dementia risk by reporting interactions between AB status and CBF on memory performance in a sample of well-characterized, cognitively normal older adults. Results suggest that differential CBF-cognition associations can be identified in healthy, asymptomatic AB positive older adults relative to AB negative individuals. Associations between higher CBF and poorer memory among AB positive older adults may reflect a cellular and/or vascular compensatory response to pathologic processes whereby higher CBF is needed to maintain normal memory abilities. Findings indicate that CBF and its associations with cognition may have utility as a reliable marker of brain function early in the AD process when interventions are likely to be beneficial.